2008
DOI: 10.1016/j.bcp.2007.06.042
|View full text |Cite
|
Sign up to set email alerts
|

“Higher order” addiction molecular genetics: Convergent data from genome-wide association in humans and mice

Abstract: Family, adoption and twin data each support substantial heritability for addictions. Most of this heritable influence is not substance-specific. The overlapping genetic vulnerability for developing dependence on a variety of addictive substances suggests large roles for "higher order" pharamacogenomics in addiction molecular genetics. We and others have now completed genomewide association (GWA) studies of DNAs from individuals with dependence on a variety of addictive substances vs appropriate controls. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 100 publications
8
99
0
1
Order By: Relevance
“…60 Of related interest, PDE4D variants that distinguish dependent versus non-dependent individuals abusing methamphetamine, alcohol, nicotine and other substances have been previously identified in several GWA studies of addiction vulnerability. 61 Given the high comorbididty of ADHD with substance use disorders, the convergence with genes identified in GWA studies of addiction vulnerability and related phenotypes provides further confidence in our data. Although previous association to ADHD has not been reported for these genes, those identified both by this study and by findings from other related reports appear especially relevant for further detailed evaluation.…”
Section: Discussionmentioning
confidence: 58%
“…60 Of related interest, PDE4D variants that distinguish dependent versus non-dependent individuals abusing methamphetamine, alcohol, nicotine and other substances have been previously identified in several GWA studies of addiction vulnerability. 61 Given the high comorbididty of ADHD with substance use disorders, the convergence with genes identified in GWA studies of addiction vulnerability and related phenotypes provides further confidence in our data. Although previous association to ADHD has not been reported for these genes, those identified both by this study and by findings from other related reports appear especially relevant for further detailed evaluation.…”
Section: Discussionmentioning
confidence: 58%
“…A previous study demonstrated that there is a genetic component for the risk of substance dependence, particularly opioid dependence (3). Consistently, family and twin studies have demonstrated a substantial genetic effect on the development of drug dependence, with inherited risk estimates in the range of 40-60% (4,5). A previous study revealed that the regulator of G protein signaling 9 (RGS9) gene may be associated with drug dependence, including opiate dependence (6).…”
Section: Introductionmentioning
confidence: 90%
“…Indeed, some twin studies suggest that about 50% of this vulnerability is heritable [1]. The Lewis (LEW) and Fischer 344 (F344) inbred and histocompatible rat strains are a useful model to approach from an experimental point of view the contribution of genetic factors in drug abuse and addiction.…”
Section: Introductionmentioning
confidence: 99%